2001
DOI: 10.1016/s0896-6273(01)00181-7
|View full text |Cite
|
Sign up to set email alerts
|

Kinase-Dependent and Kinase-Independent Functions of EphA4 Receptors in Major Axon Tract Formation In Vivo

Abstract: The EphA4 receptor tyrosine kinase regulates the formation of the corticospinal tract (CST), a pathway controlling voluntary movements, and of the anterior commissure (AC), connecting the neocortical temporal lobes. To study EphA4 kinase signaling in these processes, we generated mice expressing mutant EphA4 receptors either lacking kinase activity or with severely downregulated kinase activity. We demonstrate that EphA4 is required for CST formation as a receptor for which it requires an active kinase domain.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
199
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 237 publications
(212 citation statements)
references
References 52 publications
13
199
0
Order By: Relevance
“…All mutant Kit receptors were autophosphorylated in response to SCF in 293 cells (Fig. 5A), indicating that substitution of the Jx tyrosines does not lead to a complete failure of kinase activation, as observed for Eph receptors (20,21,30). However, tyrosine phosphorylation of the 567F and 569F single mutant receptors was reduced compared with wild-type and phosphorylation of the FF double mutant receptor was even further decreased.…”
Section: The Jx Tyrosine Mutations Cause Differences In Downstream Simentioning
confidence: 70%
See 1 more Smart Citation
“…All mutant Kit receptors were autophosphorylated in response to SCF in 293 cells (Fig. 5A), indicating that substitution of the Jx tyrosines does not lead to a complete failure of kinase activation, as observed for Eph receptors (20,21,30). However, tyrosine phosphorylation of the 567F and 569F single mutant receptors was reduced compared with wild-type and phosphorylation of the FF double mutant receptor was even further decreased.…”
Section: The Jx Tyrosine Mutations Cause Differences In Downstream Simentioning
confidence: 70%
“…These mutations might therefore uncouple a specific pathway(s) activated by tyrosine phosphorylation of residues 567 and 569 from the other pathways regulated by the Kit RTK. In contrast to Eph receptors, such as EphA4, for which substitution of the Jx tyrosines with phenylalanine results in constitutive autoinhibition of the kinase domain and a kinase inactive phenotype in vivo (30), the Kit FF mutant receptor retains partial signaling activity. These data suggest that the precise molecular mechanisms by which the Kit and Eph receptor Jx regions regulate kinase activity are likely to be distinct.…”
Section: Discussionmentioning
confidence: 90%
“…Genetic studies in vivo have shown that Eph receptors have both kinase-dependent and -independent functions (Birgbauer et al, 2000;Dalva et al, 2000;Grunwald et al, 2001;Kullander et al, 2001). In addition, some Eph receptors either have kinase-deficient variant forms generated by alternative splicing (EphA6, 7, and B1) (Zisch and Pasquale, 1997) or have kinase domains with defective catalytic activity (EphB6 and A10) (Gurniak and Berg, 1996;Manning et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Knock out studies in the mouse support the idea that signals mediated by ephrin-B1 and ephrin-B3 control axon pathfinding in the embryonic brain anterior commissure and the developing retina (13,14), whereas signals mediated by ephrin-B2 control the formation of the vascular system (15,16).…”
mentioning
confidence: 91%